018 The Implementation Field Team 6 Years On: Approaches to Engagement and Evaluating Impact. (15th August 2013) - Moore, J; Moore, V
Abstract : Background: The Implementation Field Team for this national guidance producing organisation has been established for six years. Seven consultants visit around 800 organisations annually, providing updates on national guidance, sharing examples of implementing good practice, and collecting feedback on our national guidance and barriers to implementation. Context: We have consistently evaluated our activities, but have found inherent difficulties with identifying impact, and have relied on proxy measures of success. As a new system for commissioning health services develops, we reviewed evidence around effective implementation activities and evaluating their impact. This led to innovative approaches to engagement and improved methods of evaluating impact. Description of Best Practice: We revised field team implementation strategies and activities to fit better with the new system of health commissioning. We conducted our own small scale survey, and also invited an external organisation to conduct a larger survey with field team clients to evaluate impact and to inform the planning and delivery of services in the future. We have moved from proxy measures of effectiveness evaluated every six months to newly developed "success criteria", which are outcomes focused, owned by the whole organisation, and identify three year incremental objectives for external engagement. This informs operational plans for future engagement activities. Lessons for Guideline Developers, Adaptors, Implementers, and/or Users: Evaluating the impact of implementation activities and teams is difficult but important and achievable. Focusing on immediate and intermediate implementation outcomes over longer timescales, and developing success criteria for field team implementation and engagement activities is valuable.